2013
DOI: 10.1007/s13238-013-3091-0
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the N-terminal ankyrin repeat domain of TRPV3 reveals unique conformation of finger 3 loop critical for channel function

Abstract: In all six members of TRPV channel subfamily, there is an ankyrin repeat domain (ARD) in their intracellular Ntermini. Ankyrin (ANK) repeat, a common motif with typically 33 residues in each repeat, is primarily involved in protein-protein interactions. Despite the sequence similarity among the ARDs of TRPV channels, the structure of TRPV3-ARD, however, remains unknown. Here, we report the crystal structure of TRPV3-ARD solved at 1.95 Å resolution, which reveals six-ankyrin repeats. While overall structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“…Structural studies by cryo‐electron microscopy (cryo‐EM) resulted in low‐resolution (>13 Å) structures of several TRP channels . X‐ray crystallography was also used to determine high‐resolution structures for various fragments of the TRP channels, including the ARD of the TRPV channels . But high‐resolution structures of full‐length TRP channels remained unavailable until recently.…”
Section: Introductionmentioning
confidence: 99%
“…Structural studies by cryo‐electron microscopy (cryo‐EM) resulted in low‐resolution (>13 Å) structures of several TRP channels . X‐ray crystallography was also used to determine high‐resolution structures for various fragments of the TRP channels, including the ARD of the TRPV channels . But high‐resolution structures of full‐length TRP channels remained unavailable until recently.…”
Section: Introductionmentioning
confidence: 99%
“…The first strategy was a “divide and concur” approach, which provided structures of smaller soluble domains at atomic resolution (Fujiwara & Minor, 2008; Inada et al, 2012; Jin, Touhey & Gaudet, 2006; Lau, Procko & Gaudet, 2012; Lishko et al, 2007; Phelps et al, 2008; Phelps et al, 2010; Shi et al, 2013; Yamaguchi et al, 2001). A second strategy utilized electron microscopy (EM), which revealed full-length TRP channel structures (Cao et al, 2013; Cvetkov et al, 2011; Huynh et al, 2014; Liao et al, 2013; Moiseenkova-Bell et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified numerous residues on the ARD finger 2 that are important for TRPV3 channel gating. 44 . In addition, this region of the ARD has been implicated in binding calmodulin (CaM) and ATP, and biochemical and structural studies of isolated ARDs have further identified the conserved residue K169 as being critical for ATP binding [45][46][47] .…”
Section: The Ctd Mediates Inter-protomer Contactsmentioning
confidence: 99%